Implementation of Multistructure PID-like fuzzy logic controller using FPGA - Zeyad Assi, Obaid; Sulaiman, Nasri; Marhaban, Mohammad Hamiruce; Hamidon, Mohd Nizar (The Institute of Electronics, Information and Communication Engineers, 2010)
This paper presents an implementation of Multistructure PIDFLC. Modification has been made to structure of the proposed PIDFLC in order to make it acts as PDFLC, PIFLC or PIDFLC depending on two external signals. Two versions of this controller have been designed using VHDL language for FPGA implementation. A new package has been designed in VHDL code to implement trigonometric functions and fourth-order Runge-Kutta method to test the proposed design with nonlinear systems. The controller was able to produce an output in 0.3µsec for linear plants and 0.7µsec for nonlinear plant. Therefore, the proposed controller will be able to control many systems with high sampling rate.